An Indigenous Psychosocial Intervention for the Sexuality Problem of Men in Indonesian Urban Areas: A Systematic Literature Review - Rahmi, Kus Hanna; Fahrudin, Adi (Bulletin of Counseling and Psychotherapy, 2024)
This systematic literature review aims to analyze the psychosocial and psychosexual interventions for addressing sexual health problems among men in urban areas of Indonesia, with a focus on indigenous practices such as Mak Erot. The review follows the PRISMA guidelines, involving a comprehensive search of multiple databases, selection of relevant studies, data extraction, and synthesis. List the databases and other sources searched: PubMed, Scopus, Google Scholar, and Indonesian local journals, grey literature, and reference lists of selected articles. Search term strategies with the combination used include; Psychosocial interventions", Psychosexual problems", "Male sexual health", "Indigenous treatments", "Mak Erot", and "Urban areas in Indonesia". Based on data analysis the findings highlight the significance of culturally sensitive interventions in improving sexual and mental health outcomes for men in urban Indonesian contexts.